THE EMISSION-LINE DUSTY OBJECT IRAS 07080+0605, A LESS-EVOLVED EXAMPLE OF THE RED RECTANGLE - Khokhlov, S A.; Miroshnichenko, A. S.; Zharikov, S. V,; Manset, N.; Zakhozhay, O. V.; Bilinskyi, I. O.; Grankin, K. N.; kusakin, A. V.; Omarov, C. T.; Kokumbaeva, R. I,; Reva, I. V.; Korcakova, D.; et al. (Одеські астрономічні публікації, 2020)
The all-sky survey conducted by the InfraRed Astronomical Satellite (IRAS) in the 1980’s discovered many objects with infrared excesses whose nature has not been explored until recently. IRAS07080+0605 is one of those identified in the visual spectral range with an early-type star, which shows the B[e] phenomenon. The object is puzzling, because it exhibits one of the strongest infrared excesses associated with a star of one of the lowest surface temperatures (∼8500 K) among objects with the B[e] phenomenon, an apparent combination of spectral features of dwarfs and supergiants, and the absence of a surrounding optical nebula. Our photometric and spectroscopic study shows that the object’s properties are similar to those of the famous Red Rectangle proto-planetary nebula. In this paper we describe our findings and hypotheses about the nature and evolutionary status of IRAS07080+0605